Influence of Metal Oxide Ashes on Soot Oxidation Kinetics and Nanostructure using Electron Microscopy and Thermogravimetric Analysis - P Koko; P Karin; E Saenkhumvong; C Charoenphonphanich; W Phairote; N Chollacoop; K Hanamura (My University, 2019)
According to increasingly stringent regulations on particulate emission from automotive vehicles, diesel engine must be equipped with Diesel Particulate Filter (DPF) to trap the Particulate Matter (PM) which are very harmful to human health. Diesel particulate matters are composed primarily of unburned hydrocarbon (soot) and metal oxide ashes as solid fraction. DPF can trap PM with higher filtration efficiency and the process which can burn the soot into carbon dioxide is called regeneration process. Although regeneration process can burn the soot effectively, incombustible ashes will be remained inside the DPF channel causing engine back pressure. These metal oxide ashes are mainly derived from lubricant additives, engine wear and trace metals from diesel fuel. In this article, different nanostructures of diesel soot and metal oxide ash derived by diesel blending lube oil condition were briefly compared using Transmission Electron Microscopy (TEM) image analysis. Electron Dispersive X-ray Spectroscopy (EDS) analysis was introduced to investigate the chemical composition of particulate matters. Thermogravimetric Analysis (TGA) was also conducted to compare the oxidation kinetics of pure diesel soot and the influence of metal oxide ash on soot oxidation kinetics. Contamination of metal oxide ashes promoted soot oxidation rate due to the presence of metallic additives from lube oil acting as a catalyst on soot oxidation kinetics.
Keywords: Thermogravimetric analysis; Biodiesel Production and Applications